DUAL EDUCATION AS AN EFFECTIVE TOOL FOR ENHANCING THE PROFESSIONAL COMPETENCE OF FUTURE LAWYERS - Holovko, Svitlana G. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: to analyze the organizational and legal aspects of the dual education model implementation and to substantiate its peculiarities in future lawyers’ training. Methods: applying the method of comparative analysis, the features of dual education organization in European countries in the projection on the prospects of introducing this form of higher education in our country are highlighted; using the synthesis method, the system of normative legal support of dual education in Ukraine, the main functions of its subjects as well as organizational and pedagogical conditions for effective implementation in practice are considered. Results: european experience of implementing practically oriented educational and professional training programs for future specialists is covered; it is shown that dual education is one of the promising forms of higher education in Ukraine in the context of economic crisis and changes in employment structure, as it provides for the first employment of university graduates; legal and organizational-pedagogical conditions for effective realization of dual education are substantiated; the conclusion was drawn as to the overall development of its legal and regulatory support and the prospects for its improvement, in particular, regarding the specification of the legal status of dual education subjects; the necessity of qualitative structural changes of curricula as well as educational and professional training programs for specialists in order to overcome the detachment of theory from practice. The main difficulties in implementing this education form and ways of overcoming them are described, on the example of training of future lawyers. The article highlights the need to introduce new programs, to reinforce the cooperation of educational institutions with employers, to promote their interest in the results of qualitative implementation of theoretical and practical modules of educational and vocational programs by the education recipients through information campaigns for employers and business representatives in order to involve students in production processes. It is concluded that an important condition for the effectiveness of dual education is the formation of a new culture of discipleship and educational environment, in which the practical component will be motivated by the necessary issues and will not be inferior to the academic prestige. Discussion: the prospects for the development of dual education actualize the use of foreign experience in the context of the national educational system, taking into account its features as well as cultural and educational traditions, in particular, the ratio and status of theoretical and practical components of the educational process.